A Sociology of Legal Distinctions: Introducing Contemporary Interpretations of Classic Socio‐legal Concepts. (3rd November 2017) - Přibáň, Jiří
Abstract : In this introduction to Main Currents in Contemporary Sociology of Law, I briefly comment on the current state of socio‐legal studies and sociology of law and reasons leading to this collection of essays. I subsequently focus on some general problems which constantly recur in different socio‐legal contexts, especially on the sociological critique of legal formalism and the closely related distinctions between internal and external perspectives of law and legal facts and values. Discussing these classic distinctions, I argue that they are an intrinsic part of both legal and sociological interpretations of positive law. Sociology of law, therefore, cannot resolve theoretical and methodological dilemmas associated with them, yet it can rethink and reformulate them to better understand its own position as a social science of positive law in contemporary society.